Development of a comprehensive analytical method for furanocoumarins in grapefruit and their metabolites in plasma and urine using UPLC-MS/MS: a preliminary study. (16th November 2016) - Lee, Sang Gil; Kim, Kijoon; Vance, Terrence M.; Perkins, Christopher; Provatas, Anthony; Wu, Shaowei; Qureshi, Abrar; Cho, Eunyoung; Chun, Ock K.
Abstract: To develop a comprehensive analytical method for photoactive furanocoumarins, grapefruit (whole, flesh, peel and juice) was extracted using QuEChERS (Quick, Easy, Cheap, Effective, Rugged and Safe) method. Seven furanocoumarins: bergaptol, psoralen, 8-methoxypsoralen, bergapten, 6′, 7′-dihydroxybergamottin (6′, 7′-DHB), epoxybergamottin and bergamottin were determined in grapefruit using UPLC-MS/MS. The concentrations of furanocoumarins in the plasma and urine of six healthy young adults before and after ingestion of grapefruit or grapefruit juice were also determined. Recovery rates of furanocoumarins by QuEChERS method from matrix spike sample and laboratory calibrate sample were 125.7 ± 25.4% and 105.7 ± 6.3%, respectively. Bergamottin and 6′, 7′-DHB were predominant compounds in grapefruit flesh, juice and plasma, while bergaptol and 6′, 7′-DHB were major compounds detected in the urine. The results demonstrated that bergamottin and 6′, 7′-DHB were metabolized to bergaptol. Overall, the analytical methods developed in the present study can be applied to the analysis of various furanocoumarins in plant sources and biological samples.